2021
DOI: 10.1111/anae.15482
|View full text |Cite
|
Sign up to set email alerts
|

Oral, in place of intravenous, paracetamol as the new normal for elective cases

Abstract: We read with great interest the review discussing the equivalence in efficacy between intravenous and oral administration of paracetamol in the peri-operative period [1]. Currently, there is little information regarding the overall carbon footprint of medication usage, including paracetamol. A life-cycle assessment assesses this with a 'cradle-to-grave' analysis technique that quantifies the environmental impact associated with all stages of a product's life, from raw material extraction through processing, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…We can estimate a carbon footprint for aspects of antimicrobial use such as the ancillary plastic products used for different routes of administration. A study by Myo et al [ 59 ] has shown that oral (PO) paracetamol therapy can be provided at an approximately 68-fold lower carbon footprint compared to intravenous (IV) paracetamol in glass packaging and 45-fold lower in plastic packaging. We anticipate that the relative carbon footprints of PO and IV antimicrobials would be similar.…”
Section: Four Key Principles Of Sustainable Healthcarementioning
confidence: 99%
“…We can estimate a carbon footprint for aspects of antimicrobial use such as the ancillary plastic products used for different routes of administration. A study by Myo et al [ 59 ] has shown that oral (PO) paracetamol therapy can be provided at an approximately 68-fold lower carbon footprint compared to intravenous (IV) paracetamol in glass packaging and 45-fold lower in plastic packaging. We anticipate that the relative carbon footprints of PO and IV antimicrobials would be similar.…”
Section: Four Key Principles Of Sustainable Healthcarementioning
confidence: 99%
“…By accessing the trusts contracts and using the appropriate GHG conversion factors, we were able to calculate scope 1 and 2 emissions. All additional sources of inventory reconciliation including scope 1 and 2 data can be visualised in Figure 4 [20][21][22][23].…”
Section: Additional Data Sourcesmentioning
confidence: 99%
“…Parvatker et al 2019 20 3 Secondary Carbon impact of the pharmaceuticals (except paracetamol) [20] Myo et al 2021 21 3 Secondary Carbon impact of paracetamol [21] Burguburu et al 2022 22 3 Secondary Lifecycle Carbon impact of Scrubs [22] Rizan & Lillywhite 2022 23 3 Secondary Carbon impact of sterilisation [23] Greenhouse The site has a mix of energy sources, using grid electricity, gas, and a large onsite CHP plant N/A…”
Section: Data Source Scope Type Operative Data Used Referencementioning
confidence: 99%
“…Studies have shown that there is no significant difference between intravenous (IV) and oral preparations in postoperative pain outcomes. [1,2] We proposed moving towards routine administration of oral paracetamol before surgery to reduce the use of IV preparations, with benefits of carbon and cost reduction.…”
mentioning
confidence: 99%
“…If we achieve 100% adherence, this will increase to 3,741 kg of carbon dioxide and £28,037 per year respectively. [2,3] Discussion: Routine use of preoperative oral paracetamol has resulted in a significant reduction in the use of intravenous preparations. Extrapolated across the whole hospital, there are large carbon and cost savings to be made.…”
mentioning
confidence: 99%